Analisis Program Community Based Correction dalam Sistem Pemasyarakatan untuk Rehabilitasi Narapidana - Subroto, Mitro; Admirad, Keny (Innovative: Journal Of Social Science Research, 2025)
The shift in terminology from "prison sentence" to a more humane approach in Indonesia’s correctional system reflects a paradigm shift from punishment focused on deterrence to rehabilitation and social reintegration. The correctional system, which focuses more on rehabilitation, aims to reintegrate prisoners as productive members of society, although issues such as inmate violence and limited facilities still persist. One concept that has emerged as a solution is Community-Based Correction (CBC), which offers an alternative form of punishment by involving the community in the rehabilitation process. CBC emphasizes rehabilitation, social reintegration, and restorative justice as a more humane method compared to imprisonment. This study uses a qualitative descriptive method to explore the implementation of CBC in prisoner assimilation programs. The research findings indicate that CBC helps reduce the risk of recidivism by involving prisoners in social activities outside the prison. Although it has been implemented, CBC still faces challenges in optimization, such as limited social support and employment opportunities. Therefore, strengthening this program is necessary to improve prisoner rehabilitation and accelerate their social reintegration.